Designing spaces for children a child's eye view - Dziobek-Bepler, Nathalie (Jovis, 2021)
Meeting children as equals is not only a question of pedagogical attitude. Designing Spaces for Children shows how architecture and interior design can promote childhood development. Based on historical and current concepts of progressive education, the book sketches design principles for building daycare centers and schools that can also be transferred to other spaces, such as pediatric clinics. Rooms can invite discovery; they can promote communication and social interaction, strengthen self-confidence, and be places of retreat or landscapes for play. For years, the Berlin architectural firm baukind has been creatively balancing the strict legal requirements and architectural possibilities of architecture suitable for children--always with a view to children's needs. The book presents realized projects, such as the Kita Weltenbummler in Berlin, and aims to foster the equal involvement of children in the design of our environment.